QUALITATIVE RISK ASSESSMENT OF AVIAN INFLUENZA VIRUS TRANSMISSION THROUGH INCUBATION EGGS - A. S. Oganesyan; A. V. Varkentin; N. Ye. Baskakova; A. K. Karaulov (Ветеринария сегодня)
Analysis of literature on avian influenza (AI) virus transmission through incubation eggs and qualitative assessment of risk of incubation egg import to the Russian Federation in the contest of veterinary and sanitary measures against avian influenza currently in place for imported products are presented. Probability of low-pathogenic AI virus transmission through poultry incubation eggs due to possible contamination of the egg and package surfaces with the said agents is indicated. Probability of AI virus transmission through commercial eggs derived from quails, turkeys, geese, chickens is shown to be high. Evidence of actual vertical transmission of highly pathogenic avian influenza virus is limited, however, it is recognized that the infection manifests by systemic lesions in the organs (bursa, thymus, spleen, heart, pancreas, kidneys, brain, trachea, lungs, adrenals and skeletal muscles). It is noted that the virus can persist on bird feathers and in bird meat for a long period. In addition, high humidity, neutral pH level and low temperature are shown to be favourable conditions for the virus survival in the ambient environment. Incubation egg movement restrictive measures are considered the most adequate for prevention of the disease spread between holdings. It is underlined that no country can guarantee the absence of the risk of avian influenza occurrence in avifauna. Anti-AI measures for incubation egg importation recommended by the World Organization for Animal Health are considered adequate for prevention of international disease spread regardless of the virus pathogenicity.